PENGARUH GREEN MARKETING DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PADA YAMAHA PANCA MOTOR PAGAR DEWA - Hana Syafira; Ade Tiara Yulinda Yulinda (UM. Bengkulu, 2022)
Abstract This study aims to 1) determine the effect of green marketing on purchasing decisions for Yamaha Panca Motor Pagar Dewa products. 2) Knowing the influence of lifestyle on purchasing decisions for sheren hijab products. 3) Knowing the effect of green marketing and lifestyle on purchasing decisions for Yamaha Panca Motor Pagar Dewa products. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all consumers of Yamaha Panca Motor Pagar Dewa. The sample is 140 consumers of Yamaha Panca Motor Pagar Dewa. Based on the results of research on the effect of green marketing and lifestyle on purchasing decisions at Yamaha Panca Motor Pagar Dewa. 1) The tSig value for the Green marketing variable (X1) is 0.002. So it can be concluded that tSig<Sig (0.002<0.050 ) means Ha is accepted and H0 is rejected, that the Green marketing variable affects the purchasing decision of Yamaha Panca Motor Pagar Dewa .2) The tSig value for the Lifestyle variable (X2) is 0.001. So it can be concluded that tSig<Sig (0.001<0.050 ) means Ha is accepted and H0 is rejected, that the Lifestyle variable affects the purchasing decision of Yamaha Panca Motor Pagar Dewa. 3) The hypothesis test above can be seen for the Green marketing variable (X1), and Lifestyle (X2) Fsig value = 0.004. So it can be concluded that FSig < Sig (0.004 < 0.050 ) means Ha is accepted and H0 is rejected, that each variable has a significant effect on purchasing decisions (Y) on Yamaha Panca Motor Pagar Dewa. Keywords: Green Marketing, Lifestyle, Decision,